Secure attachment Dan Kualitas Pernikahan Pada Individu Menikah: Sebuah Meta-Analisis - Konradus, Natalia; Hadjam, M. Noor Rochman; Harsanti, Intaglia; Tarigan, Avinanta (Jurnal Online Psikogenesis, 2023)
Previous studies have shown a relationship between secure attachment and marital quality in married couples. However, the correlation between secure attachment and marital quality shows varying results. This meta-analysis aims to evaluate the relationship between secure attachment and marital quality for married couples by revealing how true r is and the effect size of the correlation between the two variables. This meta-analysis research identified 15 studies that he considered eligible, with a total sample of 4.840. The results of the analysis confirm that there is a positive correlation between secure attachment and the quality of marriage in married individuals at a strong level with 95% CI [0,401; 1,053]. The heterogeneity test showed good results, and there was no publication bias.